365 things to make and do - Bolton, Vivienne (Bath : Parragon, 2004)
Presents a variety of ideas for handicraft projects that use recycled objects from around the home.
Includes index.
Keywords: Handicraft -- Juvenile literature; Decoration and ornament -- Juvenile literature